Science - Parker, Steve (Author); Riley, Peter (Consultant) (Thaxted, Essex, Miles Kelly, 2022)
Take a closer look at the incredible world of science and how it helps to shape our world. Exactly 100 facts will help you understand key scientific topics, from atoms to X-rays. Find out why acids can be dangerous, how magnets work, and why bats have super senses.